DARI SPIRITUALISME LOKAL MENUJU SPIRITUALISME ISLAM - MUHAMAD AFIF (Al Qalam, 2012)
Among the modem life tended to the materialistic, we still meet a number of a group of people in Indonesia who want to be out from the modem life by performing certain tenets and rituals in which the tenets and rituals they perform tend to be spiritual and moralistic, without having the legal-formal rules and tenets. In the study of religion, such a kind of tenet is called spiritualism movement, and in Indonesia, it is welI-known as a religious sect and mysticism. These sects, according to their founders, are established as an antithesis over the modem life that is more materialistic, the recent condition of Indonesian society who become having more moral degradation, and the elites of politics, the government, as well as the religious leaders who are seriously trapped in the formal mundane affairs. Therefore, according to them, it is necessary to introduce a form of life that gives more priority to the spiritual and psychological aspects that are not tied by any legal religion that is legally admitted by the state. However, what is offered by them, as a matter off act, is basically as their mistakes and their wrongness in understanding religious teachings, especially Islam, because the teachings they provide and develop have many similarities with Islamic spiritualism (Tasawuf), but it is understood and interpreted based on their own thought. Hence, It is necessary to transform such local spiritual movements into Islamic spiritualism (tasawuf). Key Words: beliefs, mysticism, spiritualism